Ce stabilized Ni–SrO as a catalytic phase transition sorbent for integrated CO2 capture and CH4 reforming. Issue 6 (13th January 2022) - Gu, Haiming; Gao, Yunfei; Iftikhar, Sherafghan; Li, Fanxing
Abstract : Ce stabilized Ni–SrO was proposed as a bifunctional catalyst-sorbent. CeO2 promoted a complex carbonation/decarbonation pathway to solve the sorbent stability challenges and facilitated syngas generation with tunable compositions. Abstract : Integration of carbon dioxide capture from flue gas with dry reforming of CH4 represents an attractive approach for CO2 utilization. The selection of a suitable bifunctional material serving as a catalyst/sorbent is the key. This paper reports Ni decorated and CeO x -stabilized SrO (SrCe0.5 Ni0.5 ) as a multi-functional, phase transition catalytic sorbent material. The effect of CeO x on the morphology, structure, decarbonation reactivity, and cycling stability of the catalytic sorbent was determined with TEM-EDX, XRD, in situ XRD, CH4 -TPR and TGA. Cyclic process tests were conducted in a packed bed reactor. The results indicate that large Ni clusters were present on the surface of the SrNi sorbent, and the addition of CeO2 promoted even distribution of Ni on the surface. Moreover, the Ce–Sr interaction promoted a complex carbonation/decarbonation phase-transition, i.e. SrCO3 + CeO2 ↔ Sr2 CeO4 + CO2 as opposed to the conventional, simple carbonation/decarbonation cycles ( e.g. SrCO3 ↔ SrO + CO2 ). This double replacement crystalline phase transition mechanism not only adjusts the carbonation/calcination thermodynamics to facilitate SrCO3 decomposition at relatively low temperatures but also inhibits sorbent sintering. As a result, excellent activity and stability were observed with up to 91% CH4 conversion, >72% CO2 capture efficiency and ∼100% residual O2 capture efficiency from flue gas by utilizing the CeO2 ↔ Ce2 O3 redox transition. This renders an intensified process with zero coke deposition. Moreover, the SLDRM with SrCe0.5 Ni0.5 has the flexibility to produce concentrated CO via CO2 -splitting while co-producing a syngas with tunable H2 /CO ratios.